AI and Open Badges: Discover and Share How AI Can Enhance Your Recognition Projects (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Artificial intelligence is increasingly becoming a practical companion for the design and implementation of recognition systems. In the field of Open Badges and Open Recognition, AI tools can support practitioners not by replacing human judgment, but by assisting with the many decisions involved in creating meaningful recognition practices. This contribution introduces three specialized GPT-based assistants designed to accompany different stages of recognition initiatives: OB Designer, Le Coach Badges (MEL), and Open Badges & Open Recognition. The OB Designer GPT (https://bit.ly/ob-designer-gpt) supports the design of badge systems and recognition artifacts. It helps practitioners define the purpose of a badge, formulate criteria and evidence, structure metadata aligned with Open Badges standards, and ensure coherence across badge constellations and recognition pathways. Le Coach Badges (MEL) (https://chatgpt.com/g/g-68a33cdd58d8819187e392fad3a0c299-le-coach-badges-mel) focuses on implementation. It guides organizations and project teams through the process of introducing badges, identifying recognition opportunities, engaging stakeholders, structuring pilot phases, and evaluating the impact of recognition initiatives. The Open Badges & Open Recognition GPT (https://chatgpt.com/g/g-674ae375b5e48191b035f9f1b0e9ea0f-open-badges-open-recognition) provides conceptual and strategic support. It helps users explore the principles of open recognition, peer recognition, and community-based validation, and reflects on how recognition practices can move beyond credential issuance toward richer recognition ecosystems. Together, these AI assistants illustrate how generative AI can augment recognition projects by supporting practitioners across three complementary layers: conceptual understanding, program implementation, and artifact design. Rather than prescribing a single model, the tools encourage reflective practice and context-sensitive design, helping communities and organizations experiment with recognition approaches that are meaningful, participatory, and adaptable. Keywords: AI, reflexivity, generative, technologies